Absolute Temperature Thresholds for Detection of Skin Wetness and Dampness on the Hand and their Variation with Sex and Age. (October 2021) - Kumar, Sandhya; Kumar, Surabhi
The human body has dedicated receptors for sensing temperature and touch, but not wetness. How then is wetness perceived? To test if wetness perception arises from the sensory integration of touch and temperature, and to quantify its measurement in humans, we designed a wetness perception monitor (WPM) which enabled variation of temperature at the fingertips of participants while measuring the pressure exerted on a test surface in the controlled environment of a moisture-free chamber. Thirty randomly selected adults (18+ years) were tested for their perception of dampness/wetness using the WPM. Our data suggest that humans perceive dampness and wetness at average temperatures of 22 ± 0.4°C and 18 ± 0.5°C, respectively, and these sensations are extinguished at temperatures below 16 ± 1°C. Measurements were obtained at an average tactile pressure of 1.5 ± 0.3  kPa. Young adults (18–35 years) sensed wetness at significantly higher temperatures than middle-aged adults (36–55 years) or mature adults (56+ years), who sensed wetness at similar temperatures. We found a surprising sex difference in wetness perception, with females sensing wetness at higher temperatures than males. When the data were screened for outliers, we found that participants whose readings were outside normal ranges, self-reported sensory deficits suggesting that wetness perception could potentially be used as a noninvasive biomarker.